Analysis and Design of Fiber Optic Network Between Gandul-Durentiga for Quality of Service (QoS) Enhancement - Waryani; Wismiana, Evyta; Putri, Herlina Anziani; Efendi, Dede Putra (Universitas Nusa Putra, 2024)
To achieve stable internet communication services, it is necessary to have good internet service quality. The greater the transmission capacity and bandwidth used, the faster information can be accessed from the internet. Quality of Service (QoS) is a measurement method used to determine the capability of an internet network to provide better and planned network services to meet the needs of a service. In analyzing the Design of Fiber Optic Networks for Quality of Service (QoS) improvement between Gandul and Duren Tiga, two factors need to be known, namely the Fiber Optic network and several parameters such as throughput, packet loss, jitter, and delay. In the analysis of the Fiber Optic network, the focus is on reducing losses in the network, while for parameters such as throughput, packet loss, jitter, and delay, observations are conducted using standard telephony and Wireshark applications. The results of the analysis based on the triphone standard show that the quality of throughput speed in the Gandul and Duren Tiga areas is still subpar, especially in terms of throughput. To improve some of these inadequate/poor parameters, several steps are taken, namely by adding/installing a Small Form-Factor Pluggable (SFP). By installing a Small Form-Factor Pluggable (SFP), some of these parameters can be improved, specifically in terms of throughput in the Gandul and Duren Tiga areas.